Reformation, Revolution, Renovation The Roots and Reception of the Rosicrucian Call for General Reform - de Vries, Lyke (Universal Reform, 2022)
An account of the Rosicrucian manifestos, and in particular their call for a general reformation, in relation to medieval and early modern traditions and reform programs.; Readership: All interested in early modern intellectual history, specifically in reform programs in religion, politics, and knowledge; and anyone with an interest in Reformation studies, the history of science, and Rosicrucianism. Keywords: Universal Reformation, utopia, manifestos, manifestoes, Johann Valentin Andreae, mission statements, reform programs, heterodoxy, seventeenth century, Middle Ages, esotericism, alchemy, medicine, Paracelsus, Paracelsianism, German history, astrology.